A Study of the Factors That Affect the Effectiveness of Counter Service towards Customer Satisfaction: A Case Study OF Student Affairs Division, Uitm Kedah / Mohamad Noor Faiez Mahadi...[et al.] - Mahadi, Mohamad Noor Faiez; Ibnu, Md Ilyas Syahmi; Abdul Rahim, Nazihah; Rosdi, Rabi’atul ‘Adawiyah; Mazlan, Muzdalifah (2010)
The study is done by the researchers on A Study on Factors that Affecting the Effectiveness of Counter Service towards Customer Satisfaction: A Case Study of Student Affairs Division Uitm Kedah. Satisfaction is defined as a person’s feeling of pleasure or disappointment resulting from comparing a product perceived performance or outcome in relation to his or her expectations (Kotler, 2000). The researchers state one variable in term of staff behaviour. In this research, the researchers want to know the satisfaction that is shown by the customer with their attitude after the employee serves them. It means that the researchers want to investigate how the staff’s behaviour can influence customer satisfaction. The researchers used UiTM Kedah students as the respondent in order to know the satisfaction by using questionnaire method.